Asystentura rodziny w dobie pandemii = Family assistantship in the age of the pandemic - Hyży, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Family assistantship is largely based on direct contacts with another person. Unfortunately, due to the increase in SARS COV-2 virus infections, some of the activities of family assistants have been severely limited. The purpose of the article is to present the changes that have occurred during the pandemic in the activities of family assistants as well as the difficulties and limitations they face in carrying out their duties.
Keywords: asystent rodziny; pandemia; pomoc społeczna; family assistant; pandemic; social welfare